Evaluating the in-Hospital Mortality Frequency during 30 Days among Patients with Hypoalbunemia admitted in a Tertiary Care Hospital of Karachi - Wardah Asif, Arjan Kumar, Muhammad Rehan, Hari Lal, Muhammad Tanveer Alam, Muhammad Adnan Kanpurwala (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypoalbuminemia ‎ is a strong predictor for assessing acute and chronic illness conditions. The condition of hypoalbuminemia ‎is associated with the low synthesis of albumin resulting from cachexia and wasting. Aim: To find out the frequency of 30 Day in-hospital mortality among patients with hypoalbuminemia admitted at a tertiary care hospital of Karachi. Study design: Cross-sectional study. Place and duration of study: Data was collected from the Department of Medicine Department, Government Tertiary Care Hospital of Karachi during a period of six months from Feb 2022 to August 2022. Methodology: One hundred and seven patients who met the investigative criteria were included. A short history was taken and demographic details were recorded after taking informed written consent. 5 ml of blood from a peripheral vein and collected in a specific tube to measure serum albumin level at admission. Patients with serum albumin < 3.5 mg/dl were labelled hypoalbuminemia. Patients were followed throughout the admission, and those expiring within the 30 days of admission were labelled as having 30 Day in-hospital mortality. Results: The measurements of mean age, height, albumin, ‎and weight were 49.87±12.41 years, 159.00±7.28 cm,‎1.89±0.33 mg/dl‎, and 78.7±9.87 kg, respectively. Sixty-five (60.7%) were male, and 42 (39.3%) were female. In this study, we found that the in-hospital death rate was 14%. A significant association was found between in-hospital mortality and gender, age group, diabetes mellitus, hypertension, anemia, smoking status, and family income status. Conclusion: Hypoalbuminemia ‎ is a strong predictor for assessing acute and chronic illness conditions. The plasma albumin levels were reduced during mortality and extended hospital stay. Hence, the measurement of plasma albumin should be considered during the assessment of patients with cardiogenic shock. Keywords:‎ 30 Day in-hospital mortality, ‎Hypoalbuminemia, Length of hospital stay